An Unexpected Consequence of Plastic Litter Clean-Up on Beaches: Too Much Sand Might Be Removed. (1st December 2016) - Battisti, Corrado; Poeta, Gianluca; Pietrelli, Loris; Acosta, Alicia T.R.
Abstract : We removed plastic meso- and macro-litter (PML) during a beach clean-up practice on a protected Mediterranean sandy beach in central Italy from the high tide line to a berm half-way up the beach and from the berm to a sand dune the rest of the way up the beach. Plastic fragments, cotton buds, and expanded polystyrene (EPS) fragments were the most common categories constituting about 90% of total abundance. We separated sand from PML and found that the weight of the sand was about 14% of the total weight removed. Although our data may be affected by local factors, they have general implications for management actions. Environmental practitioners who develop projects in beach cleaning should pay attention when removing PML since a significant amount of sand could be unintentionally removed resulting in unnecessary material in landfills or other disposal, and over time potentially could significantly affect sandy beaches.